The Effect of The Pancasila Student Profile Strengthening Project on Civic Skills In Students of SMA Negeri 6 Jeneponto In Jeneponto Regency - Anfar, Citra Amalia; Muhajir, Muhajir; Suardi, Suardi (JED (Jurnal Etika Demokrasi), 2024)
The Merdeka Program is an initiative to improve the quality of Pancasila Students by providing opportunities to acquire knowledge, develop skills, and improve performance in six areas of Pancasila Student profile development. Thus, citizenship skills develop from knowledge relevant to citizenship, allowing them to effectively deal with national and international issues. This citizenship skill is a skill that comes from social knowledge, which transforms the information obtained into something significant. This study aims to analyze the influence of the Pancasila Student Profile Strengthening Project on Civic Skills in SMA Negeri 6 Jeneponto students. This study used a combination observation method, which is research based on a combination of positivism and positivism. The mixed method research is a reset process that combines quantity and cauldron formats. The results of this study show that the Influence of the Pancasila Student Profile Strengthening Project on Civic Skills in students of  SMA Negeri 6 Jeneponto in Jeneponto Regency, where students have been able to instil character or attitudes related to several dimensions such as the dimension of faith and fear of God Almighty and noble character, the dimension of cooperation, the dimension of independence and the creative dimension as well as the creative dimension where students can come up with original ideas or ideas and can make something of value such as making handicrafts (tissue and colossal places) during the exhibition of the Pancasila student profile strengthening project. Moreover, in civic skills, students can see the teacher's strategy. At the beginning of the lesson, the teacher informs that active students will get additional points. In addition to these strategies, you can develop students' social and cognitive skills by having them make presentations in front of the class. You can encourage students to speak, ask questions, and convey ideas through lectures